SCIENTIFIC AND METHODOLOGICAL SUPPORT OF FINANCIAL EXPRESS ANALYSIS OF SMALL INDUSTRIAL ENTERPRISES OF UKRAINE - Liudmyla Sokolova; Viktor Dyuzhev; Ganna Veriasova; Oleksandr Kurdenko; Esknder Suliaman Salty Al-Fakhore (Сучасний стан наукових досліджень та технологій в промисловості)
The subject of research of this work is the current direction in the financial activities of small industrial enterprises – financial express analysis. The purpose of the study is to develop a scientific and methodological basis for a simplified procedure of financial supervision of small industrial enterprises in the country in order to provide qualified assistance to managers of small industrial enterprises in the financial sphere of their activities. The article solves the following tasks: study of the state of small industrial enterprises and their role in the development of Ukraine's economy, definition of "financial supervision", development of algorithm for financial express analysis of small industrial enterprises, choice of directions for financial express analysis of small industrial enterprises financial supervision, the formation of a bank of input data on four components, testing of scientific and methodological support on the example of a particular enterprise. The following methods are used: theoretical generalization, retrospective analysis, comparative analysis, analytical, analysis and synthesis, rapid analysis. The following results were obtained: the method of financial express analysis of a small industrial enterprise was proposed on the basis of financial supervision; selected areas of financial analysis under a simplified procedure; the scheme of algorithm of carrying out procedure of financial supervision is developed; the bank of the input data which are necessary for the decision of the set task is formed; substantiation of the choice of applied mathematical models is carried out; the experimental approbation of the offered scientific and methodical approach to carrying out the financial express-analysis on the factual basis of the real small industrial enterprise is carried out; appropriate recommendations were given to the management of the researched enterprise. Conclusions: It is determined that in the current unstable economic conditions, small industrial enterprises need professional assistance of consulting orientation in financial activities. Obtaining up-to-date relevant information on the financial condition of small industrial enterprises is a very important task that requires a rapid financial analysis of their activities. The study of this issue showed the lack of consensus of analysts on the directions and methods of financial rapid analysis. This led to the need and feasibility of developing for the management of small industrial enterprises under a simplified procedure of an orderly methodology of financial rapid analysis on the basis of financial supervision.